[Garran, Robert Randolph : programs and invitations ephemera material collected by the National Library of Australia]
Material in the Programs and invitations ephemera collection includes invitations to official events, dinner invitations honouring visiting dignitaries, dance cards, award presentations, openings, commemorative and sporting programs. Some programs and invitations may also include menus.
Keywords: Printed ephemera -- Australia; Invitation cards -- Australia; Programs -- Australia